2018
DOI: 10.2174/1574888x12666171002111026
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Synovium-derived Stem Cells in Cartilage Repair

Abstract: Synovium-derived stem cells possess great chondrogenic potential and showed encouraging results for cartilage repair purposes. Furthermore, synovial stem cells play an important role in joint homeostasis and possibly in natural cartilage repair. Further studies are needed to elucidate the interplay of synovial stem cells and chondrocytes, and the promising role of synovium-derived stem cells in cartilage tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 0 publications
0
55
0
Order By: Relevance
“…Articular cartilage tissue presents limited cellularity and lacks a vascular system, leading to restrained healing capability (6,7). Actually, there is no available treatment to regenerate hyaline cartilage or modify disease progression (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Articular cartilage tissue presents limited cellularity and lacks a vascular system, leading to restrained healing capability (6,7). Actually, there is no available treatment to regenerate hyaline cartilage or modify disease progression (8).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, there is no available treatment to regenerate hyaline cartilage or modify disease progression (8). Consequently, cartilage injuries are often related to pain and joint instability that may diminish or even cease the tissue's functionality (6,7). Thus, articular cartilage is at high risk of damage during initial trauma and, if left untreated, may results in lesions in the underlying subchondral bone, leading to biomechanics and homeostasis disturbances in the knee as a whole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may prove to be the optimal cell source of MSCs as native nature to the joints. Kubosch et al [58] reported that S-MSCs play an important role in joint homeostasis and possibly in natural cartilage repair. However, most of their evidence was limited to preclinical studies [61].…”
Section: Synovium-derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…4,5 Articular cartilage has limited potential for repair due to a lack of vascularity and limited cellularity. 6,7 As a consequence, cartilage injuries can result in chronic disability, 6,7 the development of osteoarthritis with significant physical limitations and decreased quality of life. 8 Among cell therapeutic solutions and regenerative techniques, there are two main examples: autologous chondrocyte implantation (ACI) and mesenchymal stem cells (MSCs).…”
Section: Introductionmentioning
confidence: 99%